Answer:
x=2
Step-by-step explanation:
Changes made to your input should not affect the solution:
(1): "x2" was replaced by "x^2".
Step by step solution :
STEP
1
:
Equation at the end of step 1
(22x2 - 16x) + 16 = 0
STEP
2
:
STEP
3
:
Pulling out like terms
3.1 Pull out like factors :
4x2 - 16x + 16 = 4 • (x2 - 4x + 4)
Trying to factor by splitting the middle term
3.2 Factoring x2 - 4x + 4
The first term is, x2 its coefficient is 1 .
The middle term is, -4x its coefficient is -4 .
The last term, "the constant", is +4
Step-1 : Multiply the coefficient of the first term by the constant 1 • 4 = 4
Step-2 : Find two factors of 4 whose sum equals the coefficient of the middle term, which is -4 .
-4 + -1 = -5
-2 + -2 = -4 That's it